2018
DOI: 10.3390/v10110630
|View full text |Cite
|
Sign up to set email alerts
|

TIM-1 Promotes Japanese Encephalitis Virus Entry and Infection

Abstract: Japanese encephalitis virus (JEV) is a mosquito-borne Flavivirus, the leading cause of viral-induced encephalitis. Several host molecules have been identified as the JEV attachment factor; however, the molecules involved in JEV entry remain poorly understood. In the present study, we demonstrate that TIM-1 is important for efficient infection by JEV. Firstly, three TIM-1 variants (V1, V2, and V3) were cloned from A549 cells, and we revealed that only ectopically TIM-1 V2 expression in 293T cells significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Given that an increase in cellular autophagy facilitates the production of many viruses, a common evolutionary selection exists among various viruses to trigger or activate autophagy [16,22]. Additionally, TIM-1 is recognized as a cellular receptor of various viruses to facilitate viral infection [39,40,41,42,43,44,45,46]. In this study, we showed a novel role of TIM-1 to activate autophagy through the TIM-1-p85 signaling axis in the early phase of DENV infection, suggesting the dependence of TIM-1 on the activation of autophagy of DENV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that an increase in cellular autophagy facilitates the production of many viruses, a common evolutionary selection exists among various viruses to trigger or activate autophagy [16,22]. Additionally, TIM-1 is recognized as a cellular receptor of various viruses to facilitate viral infection [39,40,41,42,43,44,45,46]. In this study, we showed a novel role of TIM-1 to activate autophagy through the TIM-1-p85 signaling axis in the early phase of DENV infection, suggesting the dependence of TIM-1 on the activation of autophagy of DENV infection.…”
Section: Discussionmentioning
confidence: 99%
“…TIM-1 is also known as Hepatitis A virus (HAV) cellular receptor 1 (HAVCR1), which was first identified as an HAV cellular receptor [38]. Moreover, growing evidence has proven TIM-1 to be a cellular receptor which facilitates viral infection, and existent in a number of various viruses, including Ebola virus (EBOV), Marburg virus (MARV), Lassa virus, HAV, Hepatitis C virus (HCV), JEV, and DENV [39,40,41,42,43,44,45,46]. Several findings have elucidated that TIM-1-mediated enhancement of infection mainly depends on the association of PtdSer exposed on the viral envelop [42,47].…”
Section: Introductionmentioning
confidence: 99%
“…28 In contrast, TIM-3 and TIM-4 are expressed only in antigen presenting cells (APC), where it mediates the engulfment of apoptotic bodies.The role of TIM receptors during viral infection has just been elucidated and several studies have shown its importance as a common attachment factor for a variety of enveloped viruses through direct interaction with PS of viral envelope 14,15,22,24,29. TIM-1 and -4 expression increases infection of all DENV serotypes and other flaviviruses such as YFV,14 ZIKV,30,31 JEV,32 and WNV 15 in a PSdependent manner. TIM is well described in particular for DENV infection.…”
mentioning
confidence: 99%
“…In addition to the viruses described above, recent studies demonstrated that Japanese encephalitis, hepatitis C, Tacaribe, and Ross River can use at least one of PtdSer-binding molecular mechanisms for their binding to cells [5860].…”
Section: Identification Of Molecular Mechanisms Mediating Envelope Ptmentioning
confidence: 99%